Epistolary exchange between Ricardo Rojas and Ramón Menéndez Pidal: Fragments for the construction of a post-imperial Hispanism (Anclajes, 2020)
During the first half of the twentieth century, Ramón Menéndez Pidal and Ricardo Rojas corresponded regularly about the rebuilding of political and cultural ties between Spain and Argentina following the latter’s independence. In these letters, the Spanish philologist and Rojas discussed personal news, the progress of World War I, the possibility of helping republican exiles, as well as academic topics, such as their thoughts on language, literature and folklore, the creation of the Institute of Philology at the University of Buenos Aires or the challenges to founding the Argentine Academy of Letters. Studying these texts provides insight into the history of interventions into Argentine culture during its first hundred year, a time when ties with Spain were actively being reestablished, though not without conflict.
Keywords: epistolary discourse; philology; Hispanism; cultural institutions